2018
DOI: 10.23910/ijbsm/2018.9.1.3c0908
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis for Grain Yield and its Components in Soybean (Glycine max L. Merrill)

Abstract: The present investigation was conducted with twenty two genotypes including five checks of soybean (Glycine max L.) for stability performance over three environments in a R.B.D. with three replication during kharif-2016. The analysis of variance revealed significant differences among the genotypes for all traits studied over all environments, indicating sufficient amount of variability present. G X E interaction is highly significant for all character studied except plant height, number of pods per plant and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
(1 reference statement)
1
0
0
Order By: Relevance
“…The increase in the yield parameters was due to the sulphur supplementation and availability in the vegetative and reproductive growth of the plant aiding in its chlorophyll formation, photosynthetic process and activation of enzymes and grain formation (Yadav et al 2013). The findings deduced are in line with the works carried out by Akter et al (2013); Hosmath et al (2014) and Das et al (2022) who also reported the highest seed yield in soybean due to sulphur's application at 20 kg ha -1 compared to other sulphur levels. Even though, the findings did not replicate the previously reported works concluded by Ram et al (2014) the results suggest that sulphur requirement of the crop on the experimental soil may have been satisfied at 20 kg S ha -1 and therefore further addition of increased level of sulphur was not envisaged as the higher levels of sulphur were at par (Bhattacharjee et al 2013).…”
Section: Effect Of Sulphur On Yield Attributessupporting
confidence: 77%
“…The increase in the yield parameters was due to the sulphur supplementation and availability in the vegetative and reproductive growth of the plant aiding in its chlorophyll formation, photosynthetic process and activation of enzymes and grain formation (Yadav et al 2013). The findings deduced are in line with the works carried out by Akter et al (2013); Hosmath et al (2014) and Das et al (2022) who also reported the highest seed yield in soybean due to sulphur's application at 20 kg ha -1 compared to other sulphur levels. Even though, the findings did not replicate the previously reported works concluded by Ram et al (2014) the results suggest that sulphur requirement of the crop on the experimental soil may have been satisfied at 20 kg S ha -1 and therefore further addition of increased level of sulphur was not envisaged as the higher levels of sulphur were at par (Bhattacharjee et al 2013).…”
Section: Effect Of Sulphur On Yield Attributessupporting
confidence: 77%